2007
DOI: 10.1007/s10886-007-9307-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Defense in Elodea nuttallii Reduces Feeding and Growth of Aquatic Herbivorous Lepidoptera

Abstract: The submersed macrophyte Elodea nuttallii (Hydrocharitaceae) is invasive in Europe and frequently found in aquatic plant communities. Many invertebrate herbivores, such as larvae of the generalist aquatic moth, Acentria ephemerella (Lepidoptera, Pyralidae), avoid feeding on E. nuttallii and preferably consume native species. First instar larvae exhibited a high mortality on E. nuttallii compared to the native macrophyte Potamogeton perfoliatus. Mortality of older larvae was also high when fed E. nuttallii expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
1
30
1
Order By: Relevance
“…The different types of chemical defenses can vary between species, localities, time, and environmental conditions [31]. Many of them have not been identified; some studies have found multiple dissuasive components in the chemical extracts analyzed, but the low concentrations or their unstable state makes their identification difficult and therefore their correlation with the dynamics of the aquatic community [35].…”
Section: Freshwater and Continental Environmentsmentioning
confidence: 99%
“…The different types of chemical defenses can vary between species, localities, time, and environmental conditions [31]. Many of them have not been identified; some studies have found multiple dissuasive components in the chemical extracts analyzed, but the low concentrations or their unstable state makes their identification difficult and therefore their correlation with the dynamics of the aquatic community [35].…”
Section: Freshwater and Continental Environmentsmentioning
confidence: 99%
“…Another reason is that researchers tend to regard nutrients as "therapeutic" components that always result in positive consequences whereas PSMs are considered "toxic" components with inevitable negative repercussions. As such, PSMs (Cruz-Rivera and Hay, 2003;Duffy and Paul, 1992;Felton et al, 2009;Van Alstyne et al, 2009), in others, PSMs are more important (Dearing et al, 2000;Erhard et al, 2007), and in still other cases, these factors are equally important or act synergistically to influence foraging behavior (Duffy and Paul, 1992;Frye et al in press, Simpson and Raubenheimer, 2001). While approaches, such as the geometric framework, have helped researchers study how herbivores regulate nutrient needs in variable nutritional and PSM environments (Behmer, 2009), what remains poorly understood is why certain species respond to specific thresholds of PSMs or nutrients and others do not.…”
Section: Introductionmentioning
confidence: 98%
“…by restricting angling, boating, swimming and other water-based leisure activities), for example in the reservoirs along the river Ruhr (Podraza et al, 2008). The impact of invasive species on the biodiversity of lakes can be severe and is often caused by competition with the often less robust native species or by altering the native habitat in which they reside (Barrat-Segretain, 2005;Erhard and Gross, 2006;Erhard et al, 2007;Kelly and Hawes, 2005). Weed control in aquatic habitats can be difficult, especially in Germany, where the management is limited to mechanical control methods, because chemical and biological control methods, like the use of herbicides or grass carps, are often extremely restricted or prohibited.…”
Section: Introductionmentioning
confidence: 99%